Co-assembly of sugar-based amphiphilic block polymers to achieve nanoparticles with tunable morphology, size, surface charge, and acid-responsive behavior. (11th October 2018) - Lin, Yen-Nan; Su, Lu; Smolen, Justin; Li, Richen; Song, Yue; Wang, Hai; Dong, Mei; Wooley, Karen L.
Abstract : Co-assembly of glucose-based polymers is demonstrated as a simple strategy to control nanoparticle morphology, size, surface charge, and acid-responsive properties. Abstract : The development of next-generation smart nanocarriers that can be tailored for specific applications requires precise control over physiochemical properties, yet modulation of nanostructures solely through synthetic routes is a time-consuming and labor-intensive process. In this work, co-assembly of two degradable glucose-based amphiphilic block polymers is demonstrated as a means to control nanoparticle size, surface charge, and stimuli-responsive properties, allowing optimization of these constructs for cytosolic drug delivery applications. Polymeric particles with varying weight fractions of carboxylate- and histamine-modified poly(dl- lactide)- b -poly(d -glucose carbonate)s (PDLLA- b -PDGC) were obtained with diameters ranging from ca. 30 nm to 3 μm and zeta potential values ranging from ca. −35 mV to −1.6 mV in nanopure water. Histamine moieties imparted pH-responsive behavior due to protonation below pH 7, whereas the carboxylates imparted colloidal stability and anionic character. Blending the acid- and histamine-functionalized polymers produced co-assemblies with different pH-dependent surface charge profiles. In particular, co-assemblies with 60 wt% histamine-modified PDLLA- b -PDGC ( f histamine = 0.6) swelled upon acidification from physiological pH (7.4) to endolysosomal pH (5.5), which is anticipated to enable drug release within endolysosomal compartments. The accessible procedures presented here for engineering highly tunable nanoparticles from glucose-based, functional, degradable polymers offer versatile strategies for accelerating the development and clinical implementation of such stimuli-responsive, tailored nanocarriers.